Public Option Versus the Market: Perceived Value Violations Drive Opposition to Healthcare Reform. Issue 1 (17th October 2012) - Wetherell, Geoffrey; Reyna, Christine; Sadler, Melody
<x xml:space="preserve">Abstract</x> The debate over healthcare reform in the United States has been divisive. Research demonstrates that beliefs that policy beneficiaries violate values strongly predict opposition to these policies. Similar dynamics may be happening regarding opposition to healthcare reform. Specifically, this study tested the hypothesis that opposition to a public option in healthcare reform results from stereotypes that public‐option beneficiaries violate values. In two studies utilizing three samples, beliefs about beneficiaries violating values of hard work consistently predicted opposition to a public option and an alternative market‐based healthcare reform plan, often proposed by public‐option opponents. Results also suggest that assertions that a public option would lead to bigger government increases opposition to a public option by indirectly masking underlying stereotypes about value violations.